Turnip Mosaic Virus Counteracts Selective Autophagy of the Viral Silencing Suppressor HCpro. Issue 1 (13th November 2017) - Hafrén, Anders; Üstün, Suayib; Hochmuth, Anton; Svenning, Steingrim; Johansen, Terje; Hofius, Daniel
Abstract : Potyviruses antagonize NBR1-mediated antiviral autophagy that targets RNA granules containing the viral RNA silencing suppressor HCpro for degradation. Abstract: Autophagy is a conserved intracellular degradation pathway and has emerged as a key mechanism of antiviral immunity in metazoans, including the selective elimination of viral components. In turn, some animal viruses are able to escape and modulate autophagy for enhanced pathogenicity. Whether host autophagic responses and viral countermeasures play similar roles in plant-virus interactions is not well understood. Here, we have identified selective autophagy as antiviral pathway during plant infection with turnip mosaic virus (TuMV), a positive-stranded RNA potyvirus. We show that the autophagy cargo receptor NBR1 suppresses viral accumulation by targeting the viral RNA silencing suppressor helper-component proteinase (HCpro), presumably in association with virus-induced RNA granules. Intriguingly, TuMV seems to antagonize NBR1-dependent autophagy during infection by the activity of distinct viral proteins, thereby limiting its antiviral capacity. We also found that NBR1-independent bulk autophagy prevents premature plant death, thus extending the lifespan of virus reservoirs and particle production. Together, our study highlights a conserved role of selective autophagy in antiviral immunity and suggests the evolvement of viral protein functions to inhibit autophagy processes, despite a potential trade-off in host survival.